ANALISIS SISTEM PENGUMUTAN PAJAK REKLAME TERHADAP EFEKTIFITAS PENDAPATAN ASLI DAERAH PADA DINAS PENDAPATAN DAERAH KOTA PONTIANAK - B51112061, JULIAN SAFARI (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
The purpose of this study was to determine the systems and procedures advertisement taxation implemented Pontianak Regional Revenue Office and to determine the level of effectiveness of advertisement taxation. In this research study is a form of case study method to retrieve the object of research in the Department of Revenue. The technique of collecting data using interviews and questionnaires. The analytical tool used in this research is the analysis Flowchart, Organizational Structure Analysis, Internal Control Questionnaire (ICQ) to assess the internal controls Effectiveness Analysis to measure the effectiveness of the advertisement tax on revenue. The final conclusion is that the systems and procedures advertisement taxation implemented by the Regional Revenue Office of Pontianak in accordance with Regional Regulation No. 4 of 2011 on Advertising Tax and Internal controls are implemented not run properly or there are still weaknesses in the civil service. Based on the results of the calculation of the level of effectiveness, it can be concluded that there is an increase and a decrease in tax revenue. The level of advertisement taxation yet effective that in 2015, receiving the realization by 89%, in 2012, 2013 and 2014 acceptance of the realization have been effective due to exceeding of the targets set in the amount of 105% by 2012, 102% in 2013 and 115% to 2014. by looking at actual percentage is not fixed, there are still weaknesses in the internal controls in the Department of Revenue, so it is necessary to further any improvement in the internal control system has not gone well at the Department of Revenue. Keywords: Flowchart, Internal Control Questionnaire (ICQ), Internal Control Systems.